Community-based physical activity and nutrition programme for adults with metabolic syndrome in Vietnam: study protocol for a cluster-randomised controlled trial. Issue 6 (2nd June 2016) - Tran, Van Dinh; Lee, Andy H; Jancey, Jonine; James, Anthony P; Howat, Peter; Thi Phuong Mai, Le
Abstract : Introduction: Metabolic syndrome (MetS) is a cluster of risk factors for cardiovascular diseases and type II diabetes. In Vietnam, more than one-quarter of its population aged 50–65 have MetS. This cluster-randomised controlled trial aims to evaluate the effectiveness of interventions to increase levels of physical activity and improve dietary behaviours among Vietnamese adults aged 50–65 years with MetS. Method and analysis: This 6-month community-based intervention includes a range of strategies to improve physical activity and nutrition for adults with MetS in Hanam, a province located in northern Vietnam. 600 participants will be recruited from 6 communes with 100 participants per commune. The 6 selected communes will be randomly allocated to either an intervention group (m=3; n=300) or a control group (m=3; n=300). The intervention comprises booklets, education sessions, resistance bands and attending local walking groups that provide information and encourage participants to improve their physical activity and healthy eating behaviours during the 6-month period. The control group participants will receive standard and 1-time advice. Social cognitive theory is the theoretical concept underpinning this study. Measurements will be taken at baseline and postintervention to evaluate programme effectiveness. Ethics and dissemination: The research protocol was approved by the Curtin University Human Research Ethics Committee (approval number: HR139/2014). The results of the study will be disseminated through publications, reports and conference presentations. Trial registration number: ACTRN12614000811606.